2019
DOI: 10.1080/09638237.2019.1608928
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the intimate relationship needs of service users with psychosis: what are the barriers and facilitators?

Abstract: Background: Mental health services aim to provide holistic care, but the intimacy needs of clients are neglected. Currently there is limited understanding of the challenges mental health professionals (MHPs) face when considering supporting the relationship needs of people with psychosis. Aim: This study investigated the views of community-based MHPs from a range of disciplines regarding the barriers and facilitators to supporting clients with their romantic relationship needs. Method: Semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
2
22
0
1
Order By: Relevance
“…Our results highlight a need for greater communication and assistance in the areas of intimacy and sexuality for people with psychotic disorders. Indeed, many individuals with a psychotic disorder feel that they lack the experience and the resources to engage in romantic relationships (Redmond et al, 2010; White, Haddock, & Varese, 2019). Although efforts to understand and address these issues have increased in recent years, corresponding services (e.g., intimate skill-building and couples therapy programs) are still virtually nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight a need for greater communication and assistance in the areas of intimacy and sexuality for people with psychotic disorders. Indeed, many individuals with a psychotic disorder feel that they lack the experience and the resources to engage in romantic relationships (Redmond et al, 2010; White, Haddock, & Varese, 2019). Although efforts to understand and address these issues have increased in recent years, corresponding services (e.g., intimate skill-building and couples therapy programs) are still virtually nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Negative attitudes about loneliness and mental illness from mental health professionals can also be a barrier to supporting the relationship needs of people with psychosis (e.g., having an expectation that people with psychosis will never be able to form close attachments, or that supporting relationships will be too time-consuming; White, Haddock, & Varese, 2019). On the other hand, evidence also suggests that affirming attitudes and behaviors can help to reduce stigma and promote recovery in people with psychotic disorders (Nieweglowski, Qin, Paniagua, & Corrigan, 2019).…”
Section: | Evidence-based Practice (Knowledge)mentioning
confidence: 99%
“…Miller & Byers, 2012; Quinn & Happell, 2012). A dearth of appropriate sexuality-related professional education is commonly observed across mental health disciplines and reported to contribute to clinicians’ pervasive discomfort with and avoidance of sexuality within their everyday practice (Miller & Byers, 2012; Quinn & Happell, 2012; White et al, 2019). This is often interpreted as producing a skill deficit in clinicians, which drives further research focussing on clinicians’ competence and confidence in raising and addressing sexuality in the therapeutic encounter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence of inadequate relevant training and other organizationallevel supports for clinicians suggests that their avoidance of raising and addressing sexuality-related needs may be located in the broader workplace or institution rather than an individual deficit. This is indicated by some recent studies identifying that addressing sexuality-related needs is not well embedded in practice at the organizational level and recommending that mental health clinicians must be better enabled to address these, for example, via clear guidelines and relevant proformas (Hughes et al, 2018;White et al, 2019;Zatloff et al, 2020). Higgins et al (2008Higgins et al ( , 2009 specifically demonstrated how Irish mental health nurses' practice was shaped by wider sociocultural and professional discourses that constructed sexuality as primarily reproductive (i.e.…”
Section: Introductionmentioning
confidence: 99%